Test performance study of isothermal amplification tests for the detection of Grapevine flavescence dorée phytoplasma and 'Candidatus Phytoplasma solani'. (22nd January 2017) - Mehle, N.; Kogovšek, P.; Constable, F.; De Jonghe, K.; Loiseau, M.; Veratti, F.; Marzachi, C.; Ferretti, L.; Angelini, E.; Filippin, L.; Sousa, E.; Andrade, E.; et al.
Abstract : This test performance study (TPS) was carried out on DNA samples from grapevine, clematis, fungi and bacteria to compare and validate loop‐mediated isothermal amplification (LAMP) tests for detection of Grapevine flavescence dorée phytoplasma and ' Candidatus Phytoplasma solani' (Grapevine Bois noir phytoplasma). Two LAMP tests, for Grapevine flavescence dorée phytoplasma and ' Candidatus Phytoplasma solani' (as developed by Kogovšek and colleagues), with proven applicability for rapid laboratory or on‐site detection were included in this study. They were performed in 10 laboratories. In addition, the commercial Qualiplante/Hyris isothermal amplification test for Grapevine flavescence dorée phytoplasma was performed in three laboratories. The accuracy of the three tests was shown to be over 98%. Moreover, the high accuracy of these tests, which used different devices across different laboratories, confirmed their reproducibility.